Possible Effect of Genetic Polymorphism with Thrombophilia on Brain White Matter Lesions: A Pilot Study - Şilek, Hakan; Akduman, Rana Çağla; Tuncer, Onur; Fırat, Zeynep (Cerrahpaşa Medical Journal, 2023)
Objective: The aim of this study was to determine the relationship between coincidental white matter lesions in the brain and genetic mutation in young adults without any chronic neurological disease and without risk of vascular atherosclerosis and to examine the characteristics of the lesions in brain magnetic resonance images of patients with genetic mutations. Methods: The morphology of subcortical and periventricular hyperintense white matter lesion regions were measured from high-resolution, 3-dimen- sional fluid-attenuated inversion recovery images acquired for 15 active participants. Subjects ranged in age from 30 to 55 years and were divided into 2 groups, the first was completely asymptomatic and the other was not diagnosed with a definite rheumatic disease but was divided into arthritis or serologically positive patients. Brain magnetic resonance images of the participants were measured both on a visual scale and volumetric measure- ments of detected lesions using active contour segmentation with the Insight Segmentation and Registration Toolkit (ITK)- Simple Anatomic Parsing (SNAP) viewer technique. Results: In patients who coincidentally found multiple brain white matter lesions, the most frequent gene mutations were plasminogen activator inhibitor type 1 4G/5G and methylenetetrahydrofolate reductase A1298C heterozygous. When evaluated radiologically concerning the lesion depth and configuration, they were found compatible with ischemic lesions. No statistically significant difference was demonstrated between the 2 groups in the mean volume of lesions using the semi-automated method. Conclusion: The plasminogen activator inhibitor type 1 4G/5G and methylenetetrahydrofolate reductase AC1298 C gene mutations were perceived to be one of the most common polymorphism combinations in the healthy young population that were coincidentally attested to have hyperintense white matter lesions in the brain at an early stage in an asymptomatic young population. Cite this article as: Şilek H, Akduman RC, Tuncer O, Fırat Z. Possible effect of genetic polymorphism with thrombophilia on brain white matter lesions: A pilot study. Cerrahpaşa Med J. 2023;47(2):162-167.